Protein-free domains in native and ferroptosis-driven oxidized cell membranes: a molecular dynamics study of biophysical properties and doxorubicin uptake - Shabanpour, Yaser; Hajipour-Verdom, Behnam; Abdolmaleki, Parviz; Alipour, Mozhgan (Frontiers in Molecular Biosciences, 2024)
Ferroptosis is a regulated form of cell death characterized by iron-dependent lipid peroxidation of polyunsaturated fatty acids (PUFAs). Despite its significance, the precise molecular mechanisms underlying ferroptosis remain elusive, particularly concerning their impact on membrane properties. This study aimed to investigate the biophysical changes in plasma membranes due to lipid peroxidation during ferroptosis and their impact on the uptake of doxorubicin (DOX), a potent anticancer agent linked to ferroptosis. Using all-atom molecular dynamics simulations, we compared native red blood cell membranes (protein-free domains) with a ferroptosis model, in which PUFAs were replaced with hydroperoxide derivatives. Our findings reveal that the ferroptotic membrane exhibits decreased thickness and increased lipid area while maintaining overall integrity. The hydroperoxide groups localized in the disordered tail regions, enhancing tail mobility and facilitating hydrogen bonding. Lipid lateral diffusion was significantly altered, both layers of the ferroptotic membrane exhibited slower diffusion rates compared to the native membrane. Furthermore, lipid oxidation affected diffusion activation energies. Importantly, we found that DOX could penetrate the oxidized ferroptosis membrane with a lower free-energy barrier (∆GPB) of approximately 38 kJ.mol−1. Consequently, DOX’s permeability was approximately seven orders of magnitude higher than that of the native membrane. In summary, lipid peroxidation during ferroptosis induces extensive structural and dynamic changes, influencing membrane behavior and potentially offering insights that could inform future therapeutic strategies.